The Expectations of the Members of the Aspiration Country’s Defense Forces towards Joining NATO - Jaan SILVET (Revista de Management Comparat International)
NATO has an open door policy on enlargement. Any European country in a position to further the principles of the North Atlantic Treaty and contribute to security in the Euro-Atlantic area can become a member of the Alliance, when invited to do so by the existing member countries. Joining NATO will certainly change the aspiration country’s defense forces. The current paper analyzes the expectations that the members of aspiration country’s defense forces had before joining NATO. Over 800 respondents from the aspiration country’s defense forces participated in the survey. In addition, there were conducted 5 interviews with the defense forces top executives in order to understand their perspectives on future organizational developments. As a result, there exist a gap between the expectation of top executives and other respondents. Top executives had considerably high expectations on the change of mindsets and culture of the defense forces, whereas most of the other respondents expected their equipment and everyday working conditions to improve. The analyses show also some evidence of differences in expectations of respondents between different services and agencies. The article discusses the reasons for these differences to have happened and proposes some suggestions for both NATO agencies and member state’s officials to improve the integration process with NATO.